Optimization of wear process parameters on 16-Cr Ferritic ODS steel through Taguchi approach. (2020) - Dharmalingam, G.; Mariappan, R.; Arun Prasad, M.
Abstract: Dry sliding wear was performed on a pin on disc wear testing machine by varying the process parameters such as applied load, sliding velocity and sliding distance which were performed on 16-Cr Ferritic ODS steel at high temperature (350 °C). Taguchi approach was used to analyze the process parameters for high temperature wear behavior using Signal-to-Noise ratio and analysis of variance. It was found that sliding velocity was the most significant parameters of wear rate followed by applied load and sliding distance. Regression model was obtained to find wear rate and conformation test was conducted to verify the experimental results.